2012
DOI: 10.1007/s10646-011-0849-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of biomarker responses in caged shrimps (Litopenaeus vannamei) exposed to complex contaminants from the Maluan Bay of China

Abstract: The marine shrimp Litopenaeus vannamei were used as an active biomonitoring organism to assess the bioavailability and impact of metal contaminants in seven study sites along the Maluan Bay of China. Metal concentrations in the hepatopancreas of shrimps were determined in conjunction with four biomarkers responses after a 7 day in situ cage exposures. The results showed that contaminant tissue burdens at the deployment sites were greater than those of the reference site, and antioxidant enzyme activities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The ammonia metabolism of shrimp is enhanced with exposure to a high ammonia environment, and enzymatic activities can be used as biomarkers reflecting the toxic effects of ammonia in shrimp tissues (Wang, Yan, Yan, & Chi, 2012). The present study indicated that the activities of GDH and GS and the concentration of glutamine in the shrimp tissues in each group increased in response to ammonia stress.…”
Section: Discussionmentioning
confidence: 99%
“…The ammonia metabolism of shrimp is enhanced with exposure to a high ammonia environment, and enzymatic activities can be used as biomarkers reflecting the toxic effects of ammonia in shrimp tissues (Wang, Yan, Yan, & Chi, 2012). The present study indicated that the activities of GDH and GS and the concentration of glutamine in the shrimp tissues in each group increased in response to ammonia stress.…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to an enriched ammonia environment, tissues in cultured shrimps have unique metabolic pathways for ammonia metabolism (Chang et al, 2015 ). Enzymatic activities can be applied as specific and fast biomarkers to identify toxic effects in shrimp (Wang et al, 2012 ). In most cases, studies only focused on the activities of irrelevant enzymes involved in the immune response, but not the ammonia-metabolizing enzyme (Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a biomonitoring organism, L. vannamei is commonly used to assess the bioavailability and impact of contaminants in marine environments (Keating et al, 2007 ). Wang et al ( 2012 ) suggested that the incorporation of biomarkers with the analysis of an IBR can be a useful tool for the identification of toxic contaminants in L. vannamei . Here, the total IBR index fit the strain tolerability accurately in both the hepatopancreas and the muscle with the increase in ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of sediment contamination on biota can be determined by the measurement of biomarkers [ 18 ]. Biomarkers can provide sensitive and biologically relevant information and can serve as an integrative measure of the effects of mixtures of chemical stressors [ 25 , 26 ]. Another advantage of using biomarkers lies in their potential to anticipate damage at higher levels of biological organization before ecological disruption occurs [ 27 ].…”
Section: Introductionmentioning
confidence: 99%